DISCRETE LATTICE ELEMENT APPROACH FOR ROCK FAILURE MODELING (Advances in Civil and Architectural Engineering, 2021)
This paper presents the ‘discrete lattice model’, or, simply, the ‘lattice model’, developed for rock failure modeling. The main difficulties in numerical modeling, namely, those related to complex crack initiations and multiple crack propagations, their coalescence under the influence of natural disorder, and heterogeneities, are overcome using the approach presented in this paper. The lattice model is constructed as an assembly of Timoshenko beams, representing the cohesive links between the grains of the material, which are described by Voronoi polygons. The kinematics of the Timoshenko beams are enhanced by the embedded strong discontinuities in their axial and transversal directions so as to provide failure modes I, II, and III. The model presented is suitable for meso-scale rock simulations. The representative numerical simulations, in both 2D and 3D settings, are provided in order to illustrate the model’s capabilities.